2018
DOI: 10.1016/j.physletb.2018.08.067
|View full text |Cite
|
Sign up to set email alerts
|

Connection between diphoton and triboson channels in new physics searches

Abstract: Diphoton channel provides a clean signature in searches for new physics. In this paper, we discuss a connection between the diphoton channel (γγ) and triboson channels (Zγγ, ZZγ, W W γ) imposed by the SU (2) L × U (1) Y symmetry of the Standard Model (SM) in certain classes of models. To illustrate this idea we choose a simple model that has all these channels. In this model, the same physics can give rise to γ+MET instead of γγ and 2 bosons plus missing energy instead of 3-boson channels. We analyze existing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…For 3,000 fb −1 of data, the discovery reach was found to be g aγγ ∼ 5 × 10 −4 GeV −1 , for m a from 10 MeV to 100 GeV. There are several other studies along these lines: mono-gauge-boson (including mono-photon) signatures were proposed in the search for ALP signals by [373,398]; ALPs interacting with electroweak gauge bosons have been studied by for example [401]; it has been suggested that non-resonant ALP-mediated diboson production could be a promising channel due to the derivative nature of ALP couplings [402]; and it has been claimed that a triboson search would be useful in the search for ALPs giving rise to boosted four photons which appear diphoton-like [403].…”
Section: Collidermentioning
confidence: 99%
“…For 3,000 fb −1 of data, the discovery reach was found to be g aγγ ∼ 5 × 10 −4 GeV −1 , for m a from 10 MeV to 100 GeV. There are several other studies along these lines: mono-gauge-boson (including mono-photon) signatures were proposed in the search for ALP signals by [373,398]; ALPs interacting with electroweak gauge bosons have been studied by for example [401]; it has been suggested that non-resonant ALP-mediated diboson production could be a promising channel due to the derivative nature of ALP couplings [402]; and it has been claimed that a triboson search would be useful in the search for ALPs giving rise to boosted four photons which appear diphoton-like [403].…”
Section: Collidermentioning
confidence: 99%